TRANSFORMASI PPSDM APARATUR PERHUBUNGAN MENUJU CORPORATE UNIVERSITY - Nelson Barus (ITB AAS INDONESIA Surakarta, 2021)
The changes of global conditions and the development of industrial revolution 4.0 are occurring at a very fast rate and in such a complex way, thus impacting on many resources in the transfortation sector hare to be able to anticipate this change, especially civil service (ASN) is required to be more adaptive, agile and professionall. PPSDMAP as a learning and training institution needs to perform corrections and service improrements in order to achleve the organitation’s vision and mission. In the future, PPSDMAP should function not only as a training center, nor as a tactical body to fill competency gaps, but it needs to be upgraded to become a strategic business center for develoving competent civil service and encourasing to optimize their potentials through Continuons Learning and Learning Organization. This studi is carried out in PPSDMAP and addressing the issue of whether PPSDMAP has the potential to become a learning organization and Corporate University, along with the challenges and abstracts that are present. The instrument used in this study is questionnaire rejarding Learning Organization profile which was developed M. Marquardt in his book “Building The Learning Organization”. This study encludes that PPSDMAP has the potential to become a Corporate University throught hard work and story commitment from all staker holders, particularly the leaders of PPSDMAP Keywords: Learning Organization; Corporate University